Bullous pemphigoid induced by dipeptidyl peptidase‐4 inhibitors. Eight cases with clinical and immunological characterization. (23rd April 2018) - García‐Díez, Irene; Ivars‐Lleó, Marta; López‐Aventín, Daniel; Ishii, Norito; Hashimoto, Takashi; Iranzo, Pilar; Pujol, Ramon M.; España, Agustín; Herrero‐Gonzalez, Josep E.
Abstract: Background: Dipeptidyl peptidase‐4 (DPP‐4) inhibitors have increasingly been identified as causative agents of bullous pemphigoid. The clinical and immunological characteristics of this pemphigoid variant are still unclear. The objective of our study was to analyze the clinical and immunological features of patients with pemphigoid induced by DPP‐4 inhibitors. Methods: All patients diagnosed with DPP‐4 inhibitor‐associated bullous pemphigoid at dermatology departments in three Spanish centers during the period 2013 to 2015 were included. ELISA assays for the NC16A domain of BP180 and BP230 were performed. Immunoblot studies using epidermal/dermal extracts and the C‐terminal, NC16A and LAD‐1 regions of BP180 were also carried out. Results: A total of eight patients were identified (5 treated with vildagliptin, 2 with linagliptin, and one with sitagliptin). Of these, four presented the classical inflammatory phenotype of bullous pemphigoid and four a noninflammatory phenotype. The ELISA for BP180 (NC16A domain) was positive in six patients at diagnosis. Most patients reacted to more than one BP180 antigenic site (LAD‐1 and/or C‐terminal domain) on the immunoblot. Two patients showed no reaction against the NC16A domain of BP180 on either the ELISA or immunoblot but recognized either LAD‐1 or both LAD‐1 and the C‐terminal domain. Only one of the NC16A‐negative patients had a noninflammatory subtype of bullous pemphigoid. Conclusions: Patients with DPP‐4 inhibitor‐induced BP may present either an inflammatory or a noninflammatory phenotype of BP. IgG response against other BP180 regions different from the NC16A domain, such as LAD‐1 and the C‐terminal domain, could be pathogenically relevant to the onset of DPP‐4 inhibitor‐induced BP.